Boosting visible-light-driven hydrogen evolution of covalent organic frameworks through compositing with MoS2: a promising candidate for noble-metal-free photocatalysts. Issue 35 (13th August 2019) - Gao, Meng-Yao; Li, Chang-Cheng; Tang, Hong-Liang; Sun, Xiao-Jun; Dong, Hong; Zhang, Feng-Ming
Abstract : A series of ultrathin MoS2 nanosheet decorated ketoenamine-based COF (TpPa-1) photocatalysts show excellent photocatalytic activity under visible light irradiation without noble-metal co-catalysts. Abstract : Covalent Organic Frameworks (COFs) as an emerging class of crystalline and porous materials have exhibited excellent visible-light-driven H2 generation activity in more recent years. However, noble metal co-catalysts are inevitable even in all COF-based photocatalysts to realize a high hydrogen evolution rate. In this work, for the first time we present a noble-metal free but more efficient COF-based photocatalytic H2 evolution system. We chose a typical ketoenamine-based TpPa-1-COF as a model and integrated it with MoS2 to construct MoS2 /TpPa-1-COF composites by in situ growth of the TpPa-1-COF in an exfoliated MoS2 dispersion solution of N, N -dimethylformamide (DMF). The results of photocatalytic H2 evolution under visible light irradiation show that the MoS2 /TpPa-1-COF composite with an optimized amount of 3 wt% MoS2 loading exhibits a H2 evolution rate of 55.85 μmol h −1 (10 mg photocatalyst) without any noble metal in the catalytic system, and the apparent quantum efficiency is 0.76% at 420 nm. In comparison, this H2 evolution rate of the MoS2 -3%/TpPa-1-COF composite is 32 times as high as that of the pure TpPa-1-COF (1.72 μmol h −1 ) and even a little better than that of the Pt/TpPa-1-COF (54.79 μmol h −1 ) with the same Pt loading (3 wt%). Further investigation demonstrates that MoS2 in the composite, acting as an effective non-noble-metal co-catalyst, can enormously facilitate the transfer of photogenerated electrons from the COF to MoS2 and improve the separation of photogenerated charges, leading to the excellent H2 evolution activity of the resulting composite. Considering the promising future of COF-based photocatalysts and the first report of noble-metal-free photocatalysts of COFs, this work may provide an avenue for the further design and synthesis of low-cost COF-based photocatalysts for efficient H2 evolution.